Development of a Roadmap for the Development of Learning and Teaching Profession - Bachtiar Syaiful Bachri; Himawan Wismanadi; Martadi Martadi; Nanik Indahwati; Meirinawati Meirinawati; Julianto Julianto (IJORER : International Journal of Recent Educational Research, 2022)
The Institute for Learning Development and Quality Assurance (LDQA) Universitas Negeri Surabaya (i.e Unesa) is one of the Unesa environmental organs that has the task and function of maintaining and improving the quality of Unesa learning and also as a reference for learning activities at related educational institutions. This research was conducted using a quantitative descriptive approach. The subjects of this research consist of 3 targets, namely: 1) General LDQA Management, 2) Learning Development Sector, and 3) Professional Development Sector. In this study, for the first and second problems, data were collected using documents, interviews and focus group discussions (FGD). The data obtained were analyzed descriptively qualitatively and quantitatively. Based on the results and discussion, it can be concluded that the roadmap for the Institute for Learning Development and Quality Assurance, for Professional Development for LDQA Unesa Educators and for Learning for LDQA Unesa has been prepared by accommodating the field of study which is the main task and function to answer the challenges of current and future learning needs. As for suggestions to improve achievement, it is necessary to increase cooperation with external parties who are institutionally closely related, namely dit. Belmawa, directorate general of higher education, directorate general of TOEP, education office, related institutions in accordance with LDQA's main duties and functions.